Res Judicata in Civil, Economic and Criminal Proceedings in Ukraine - CHORNOUS, Yuliia; VOLKOVA, Nataliia; ZGHAMA, Antonina; TSAL-TSALKO, Yuliia; TSYBULSKA, Olha (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The need to improve the efficiency of the implementation of the tasks of the judiciary, which is associated with the improvement of evidentiary activities, the saving of procedural time, as well as the use of res judicata (also known as claim preclusion) in the process of proving, determines the relevance of the analysis of the use of res judicata in civil, economic and criminal proceedings in Ukraine. The purpose of the article is to study the legal category of ‘res judicata’ (claim preclusion), problems of the theory and practice of the application of claim preclusion and its use in the exercise of evidentiary activity in civil, economic and criminal process, as well as the study of the limits of the application of claim preclusion. The methodological base is comprised of such methods as the dialectical, the systematic analysis of legal norms, the comparative legal, and the logical-normative method. The study of the res judicata requires the implementation of mechanisms that ensure the impartiality of justice and the unity of the case law, providing analysis of the case law and common standards for the implementation of legal proceedings, the purpose of which is to protect the violated rights and freedoms of natural and legal persons, to improve the legislation in the direction of harmonization of normative-legal acts of national legislation with international standards.